Scaling up specialist training in developing countries: lessons learned from the first 12 years of regional postgraduate training in Fiji - a case study - Oman Kimberly; Rodgers Elizabeth; Usher Kim; Moulds Robert (BMC, 2012)
Abstract Background In 1997, regional specialist training was established in Fiji, consisting of one-year Postgraduate Diplomas followed by three-year master's degree programs in anesthesia, internal medicine, obstetrics/gynecology, pediatrics and surgery. The evolution of these programs during the first 12 years is presented. Case description A case study utilizing mixed methods was carried out, including a prospective collection of enrolment and employment data, supplemented by semi-structured interviews. Between 1997 and 2009, 207 doctors (113 from Fiji and 94 from 13 other countries or territories in the Pacific) trained to at least the Postgraduate Diploma level. For Fiji graduates, 29.2% migrated permanently to developed countries, compared to only 8.5% for regional graduates (P <0.001). Early years of the program were characterized by large intakes and enthusiasm, but also uncertainty. Many resignations took place following a coup d'etat in 2000. By 2005, interviews suggested a dynamic of political instability initially leading to resignations, leading to even heavier workloads, compounded by academic studies that seemed unlikely to lead to career benefit. This was associated with loss of hope and downward spirals of further resignations. After 2006, however, Master's graduates generally returned from overseas placements, had variable success in career progression, and were able to engage in limited private practice. Enrolments and retention stabilized and increased. Discussion and evaluation Over time, all specialties have had years when the viability and future of the programs were in question, but all have recovered to varying degrees, and the programs continue to evolve and strengthen. Prospective clarification of expected career outcomes for graduates, establishment of career pathways for diploma-only graduates, and balancing desires for academic excellence with workloads that trainees were able to bear may have lessened ongoing losses of trainees and graduates. Conclusions Despite early losses of trainees, the establishment of regional postgraduate training in Fiji is having an increasingly positive impact on the specialist workforce in the Pacific. With forethought, many of the difficulties we encountered may have been avoidable. Our experiences may help others who are establishing or expanding postgraduate training in developing countries to optimize the benefit of postgraduate training on their national and regional workforces.